Fresco Paintings of the “Nobleman’s House” in the Low City of Novogrudok (after the Collection of the Plaster Fragments) - Vasil’ev, Boris G.; Jolshin, Denis D. (Actual Problems of Theory and History of Art, 2017)
The article is considering the collection of 200 fragments of fresco plaster from the 1960–1962 excavations of the 12th century “nobleman’s house” (“povalusha”) in Novogrudok, kept in the State Hermitage museum and in the National Historical museum of Belarus. These fragments present the unique Old Rus’ ensemble of the fresco painting on plaster (lime and crushed brick), which covered the secular wooden building.The study made by the author of the excavations (Frida Gurevich), and the reconstruction of the system of the paintings (Yury Spegal’sky) has been adjusted on the base of the collection and field documentation. The overallsquare of the fragments is less than 1.5 m2. It is stated that only a small part of the hut was covered by fresco plaster, including the zone of the window or the door opening since a dozen fragments have the 45 degrees angle between the surfaces. The main color of the background was red, limited by the ornamental stripes of the kymation, which differ in their shape, scale, and color. The unique figurative fresco fragment depicts a man’s head, presumably a musician, who was the part of a secular scene. The paintings were accompanied by the oneline inscription.